Sampling Volcanic Plume Using a Drone-Borne SelPS for Remotely Determined Stable Isotopic Compositions of Fumarolic Carbon Dioxide - Tsunogai, Urumu; Shingubara, Ryo; Morishita, Yuhei; Ito, Masanori; Nakagawa, Fumiko; Yoshikawa, Shin; Utsugi, Mitsuru; Yokoo, Akihiko (Frontiers in Earth Science, 2022)
Both chemical and isotopic compositions of concentrated volcanic plumes are highly useful in evaluating the present status of active volcanoes. Monitoring their temporal changes is useful for forecasting volcanic eruptions as well. Recently, we developed a drone-borne automatic volcanic plume sampler, called SelPS, wherein an output signal from a sulfur dioxide (SO2) sensor triggered a pump to collect plume samples when the SO2 concentration exceeded a predefined threshold. In this study, we added a radio transmission function to the sampler, which enabled our operator to monitor real-time SO2 concentration during flights and thus obtain more concentrated volcanic plume samples through precise adjustment of the hovering position. We attached the improved SelPS to a drone at Nakadake crater, Aso volcano (Japan), and successfully obtained volcanic plume samples ejected from the crater more concentrated than those obtained by using previous version of SelPS in 2019. Additionally, we found a significant linear correlation between the reciprocal of the concentration and isotopic ratios for the 2H/1H ratios of H2, 18O/16O ratios of CO2, and 13C/12C ratios of CO2 within the plume samples. Based on the isotopic ratios of fumarolic H2 (δ2H = −239 ± 6‰) and fumarolic CO2 (δ13C = −3.58 ± 0.85‰ and δ18O = +22.01 ± 0.68‰) determined from the linear correlations, we estimated the apparent equilibrium temperatures (AETs) with magmatic H2O simultaneously and precisely for the first time in erupting volcanoes, assuming hydrogen isotope exchange equilibrium between H2 and H2O (AETD = 629 ± 32°C) and oxygen isotope exchange equilibrium between CO2 and H2O (AET18O = 266 ± 65°C). We found that the AET18O was significantly lower than the AETD in the crater. While the temperature of the magmatic gases was originally 600°C or more, most of the gases cooled just beneath the crater to temperatures around the boiling point of water. The improved SelPS enable us to determine both AETD and AET18O in eruptive volcanoes, wherein fumaroles are inaccessible. Simultaneous and precise determination of both the AET18O and AETD can provide novel information on each volcano, such as the physicochemical conditions of magma degassing and the development of fluid circulation systems beneath each volcano.